Gambaran Pengetahuan Ibu Bersalin tentang Perdarahan Postpartum - Putri Yayu; Jumriani Jumriani; Tri Yubiah; Putri Putri (Jurnal Sehat Mandiri, 2025)
Maternal death is defined as the death of a woman while pregnant or within 42 days of the termination of pregnancy, regardless of the duration or site of the pregnancy, from any cause related to or aggravated by the pregnancy or its management. Data from Jatibaru Public Health Center showed that the incidence of postpartum hemorrhage was 7 cases out of 519 deliveries in 2021, increased to 10 cases out of 494 deliveries in 2022, decreased to 7 cases out of 439 deliveries in 2023, and reached 67 cases during the period of January to May 2024. This study aims to describe the knowledge of postpartum mothers about postpartum hemorrhage in the working area of Jatibaru Public Health Center, Bima City, in 2024. This descriptive study involved a population of 67 postpartum mothers. A total of 40 respondents were selected using a simple random sampling technique based on Slovin’s formula. The results showed that most mothers were in the non-risk age group (20–35 years), accounting for 38 respondents (95%). Most had a high school to college level of education, totaling 33 respondents (82.5%). However, the majority of respondents (25 people or 62.5%) had poor knowledge about postpartum hemorrhage. Conclusion: Most postpartum mothers in the working area of Jatibaru Public Health Center had poor knowledge regarding postpartum hemorrhage, despite being in the non-risk age group and having relatively high education levels. Recommendation: The health center should enhance education and counseling efforts for pregnant and postpartum women on the signs, dangers, and management of postpartum hemorrhage to reduce complications and maternal mortality.